Information Security in the National Security System in the Modern Age - Hussein Vakhaevich Idrisov (Fiat Justisia: Jurnal Ilmu Hukum, 2022)
The article is devoted to the legal analysis of information security as an important regulatory institution in the modern digital age. Relevance of the study is that information and its sources, as well as the means of its protection are, without a doubt, the most important tool for influencing political, economic, socio-legal and other processes in the globalized world today. Of course, in light of the recent events, information security is also one of the key elements of the national security of any state.It is emphasized separately that ensuring information security in the national security system of the state at the present stage of development of this institution is a guarantee that the activities of state structures in this area will be the most effective and systematic. The objective of the work is to conduct a scientific, legal and regulatory analysis of such important categories that form the institution of information security such as: information, security, as well as formulating the author's definitions under study.The methodological basis of the work is the following methods: synthesis, induction, deduction, as well as a number of special methods of scientific knowledge: historical, linguistic, comparative legal, formal legal.Finally, a number of conclusions are formulated and the author's definitions of the studied scientific and legal categories are given.